A Remarkable Chord Iterative Method for Roots of Uncertain Multiplicity - Fried, I. (Scientific Research Publishing, 2016)
In this note we at first briefly review iterative methods for effectively approaching a root of an unknown multiplicity. We describe a first order, then a second order estimate for the multiplicity index m of the approached root. Next we present a second order, two-step method for iteratively nearing a root of an unknown multiplicity. Subsequently, we introduce a novel chord, or a two- step method, not requiring beforehand knowledge of the multiplicity index m of the sought root, nor requiring higher order derivatives of the equilibrium function, which is quadratically convergent for any , and then reverts to superlinear.
Keywords: Iterative Methods; Unknown Root Multiplicity; Two-Step Methods